ANALYSIS OF THE INFLUENCE OF MOTOR VEHICLE TAXPAYER COMPLIANCE KNOWLEDGE USING MULTIPLE LINEAR REGRESSION - Berta Agus Petra; Silvia Sari; Lusian Lusiana; Lia Lavenia (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
Background : In 2018 the number of motor vehicle taxpayers registered in the SAMSAT of Padang City was 771,803, but those who paid taxes were only 616,748 taxpayers or 79.91%, in 2019 the number of taxpayers increased to 890,817, but those who obeyed paying taxes were 663,213 or 74.45% and in 2020 the number of taxpayers is 967,504 taxpayers and those who pay taxes are 613,978 or 63.46%. Method : Regression analysis is used to see the effect of independent variables: taxpayer knowledge (X1), taxpayer awareness (X2), motor vehicle tax sanctions (X3) and taxpayer income (X4) simultaneously on the dependent variable: taxpayer compliance (Y) with the assumption that other independent variables are considered constant. Result : Taxpayer awareness has an effect on and taxpayer compliance. The more aware taxpayers are of the importance of paying taxes, making taxpayers more obedient in paying taxes, taxes paid by taxpayers will be reused by taxpayers in the form of state facilities. Conclusion : There is a simultaneous significant positive effect between taxpayer knowledge, taxpayer awareness, motor vehicle tax sanctions and taxpayer income on motor vehicle taxpayer compliance at the Padang City SAMSAT Office, where the significant value is 0.000 <0.05.